Marching to the Beat of Her Drum: A View into the Music Heritage of the Women's Army Corps - (:unkn) unknown (My University, 2022)
The Women’s Army Corps (WAC) Band was a unique military band that consisted of all-women soldier musicians. This study examined the stories and music education of the women who served in the WAC band. Several questions guided this study including: 1) what kind of music education did these women receive before, during, and after serving in the WAC band? 2) how were the music educations of these soldiers different throughout the various eras of war? 3) did the women continue to play their instruments after they finished serving in the Army? If so, in what capacity did they play? and 4) why do they continue to hold/attend reunions every other year? The research revealed common themes across the women veterans’ lives including the desire for personal choice, changes in military protocol, women’s rights, the importance of music, as well as the sisterhood that serving in the military together created.
Keywords: Music Education; WAC; WAC Band; Women's Army Corps; Women's Army Corps Band